Serum antibodies in Campylobacter enteritis. - Kaldor, J (1983)
A solid-phase enzyme immunoassay method for the measurement of total and class-specific serum antibodies to Campylobacter jejuni was developed. The test was found to be both sensitive and specific. Immunoglobulin M, G, and A antibodies were detected in about 90% of sera collected from patients recovering from Campylobacter enteritis, with the pattern of appearance and decline of these antibodies conforming to that usually seen in an acute infection. A poor antibody response was noted in patients with intermittent or prolonged enteritis. The clinical implications and diagnostic value of this test are discussed.